Gambaran Minat Mahasiswa Keperawatan Untuk Melanjutkan ke Jenjang Profesi Ners di STIKES WIRA MEDIKA BALI - Ni Komang Tri Padma Canti; Ni Luh Putu Dewi Puspawati; Ni Made Nopita Wati (Bali Health Published Journal, 2021)
Background : The professional nursing education is part of national education whose education pattern consist of 2 stages such as academic education and profession education. The professional nursing practice can be done by nurses which has taken a bachelor’s degree in nursing and profession along obtained STR. This is a challenge for collage student so the choice appears for continue to the profession or not. Consideration for continuing to the profession stage is one of which is influenced by the interest. Interest is a basic things for direct someone to something that they liked and done so that someone can be excited. Interest consist of 2 factors there are intrinsic interest factor and extrinsic interest factor. Intrinsic interest factor is a interest factor that arise in individuals while extrinsic interest factor is a interest factor that arise by influence from outside the individual. Objective : This research aims to know the description of interest nursing collage student for continue to stage Ners profession at STIKes Wira Medika Bali. This research uses a Total Sampling technique. Data collection using the likert scale questionnaire. Results : The research result showing most of the collage student have a high intrinsic interest factor and extrinsic interest factor. Intrinsic interest factor of 66,7% and extrinsic interest factor of 72%. Conclusion : Nursing collage student at STIKes Wira Medika Bali generation IX semester VIII most of the have hight interest for continue to stage Ners profession.